Knee Muscle Reciprocal Co-Activation in Patellofemoral Pain Syndrome During Isokinetic Exercise: A Voluntary Response Index Analysis - Khaleghi, Fahimeh; Olyaei, Gholam Reza; Talebian, Saeed; Malmir, Kazem; Bagheri, Hosein; Ansari, Noureddin Nakhostin; Jalaie, Shohre (Journal of Clinical Physiotherapy Research, 2016)
Introduction: The origin of the Patellofemoral Pain Syndrome (PFPS) is not still completely clear and may have a biomechanical or biochemical cause. Motor control dysfunction may have a role in this condition. Voluntary Response Index (VRI) is able to show changes in the central nervous system motor output that occur with intervention, recovery, or progression of the disorder. Therefore, the outcomes may contribute to offer another tool for PFPS motor control evaluation. The aim of the present study, therefore, was to assess the changes in the quadriceps and hamstring reciprocal coactivation patterns that may be observed in individuals with PFPS using the VRI. Methods and Materials: A total of 24 female participants, 12 with sound knees and 12 with PFPS participated in the present study. The study was accomplished in the Biomechanics Laboratory at Rehabilitation School of Tehran University of Medical Sciences in 2015. The participants sat on a Biodex dynamometer. They were asked to perform 10 continuous knee extension and flexion motions with maximal strength at 45˚/s and 300˚/s, distinctly. Simultaneously, electromyographic activities of the vastus medialis (VM), vastus lateralis (VL), rectus femoris (RF), and biceps femoris (BF) were recorded and VRI was calculated. A two-way analysis of variance was run to assess the effect of group and velocity on the VRI (similarity index and magnitude). Results: There was no velocity or group main effect observed for the VRI (P>0.05). In addition, no significant velocity × group interaction was found for the VRI (P>0.05). Conclusion: PFPS may not be linked to altered quadriceps and hamstring reciprocal co-activation patterns during isokinetic exercise. In addition, angular velocity may not be an important parameter in voluntary motor control assessment during isokinetic exercise. Keywords: Reciprocal co-activation; Voluntary response index; Patellofemoral pain syndrome; Isokinetic